Determinants of lifetime unemployment: A micro data analysis with censored quantile regressions - Achim Schmillen; Joachim Möller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
The empirical literature on unemployment almost exclusively focuses on the duration of distinct unemployment spells. In contrast we use a large German administrative micro data set for the time span 19752004 to investigate individual lifetime unemployment (defined as the total length of all unemployment spells over a 25-year period). This new perspective enables us to answer questions regarding the long-term distribution and determinants of unemployment for West German birth cohorts 19501954. We find that lifetime unemployment is highly unevenly distributed and employ censored quantile regressions to show that, for men, pursuing a disadvantageous occupation early in the professional career leads to a significantly higher amount of lifetime unemployment. – – Die empirische Arbeitsmarktliteratur beschäftigt sich fast ausschließlich mit der Dauer einzelner Arbeitslosigkeitsperioden. Im Gegensatz dazu nutzen wir einen umfangreichen administrativen Mikrodatensatz für die Zeitspanne 1975-2004 zur Untersuchung von individueller Lebensarbeitslosigkeit (definiert als die gesamte Länge aller Arbeitslosigkeitsperioden über einen 25-jährigen Zeitraum). Diese neue Perspektive erlaubt uns, Fragen zur langfristigen Verteilung und Determinanten der Arbeitslosigkeit für die westdeutschen Geburtskohorten 1950-1954 zu beantworten. Wir finden, dass Lebensarbeitslosigkeit sehr ungleich verteilt ist und verwenden zensierte Quantilsregsressionen um zu zeigen, dass für Männer das Ausüben eines ungünstigen Berufs in der Anfangsphase der Erwerbskarriere zu einem signifikant höheren Umfang an Lebensarbeitslosigkeit führt,
Keywords: J64; J24; 330; lifetime unemployment; censored quantile regressions; occupation-specific human capital